PENGARUH APLIKASI RHIZOCTONIA MIKORIZA DAN INTERVAL WAKTU PEMBERIAN AIR PADA PERTUMBUHAN SEEDLING ANGGREK Dendrobium stockelbuschii Schettler - Daryanti; Setie Herieni; R. Soelistijono; Sari M; T Supriyadi; T.S. Kurnia Dewi (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2021)
Orchid was an ornamental plant cultivated by tissue culture (in vitro). This was because the seeds in orchid plants do not have food reserves (endosperm) to support their growth, so the plants only get nutrients and nutrients from the culture media. The propagation of orchid plants by tissue culture causes these plants do not naturally have Rhizoctonia mycorrhiza so that further plant growth in nature vegetatively and generatively will not be optimal. In this study, Rhizoctonia mycorrhiza was inoculated from species of orchids on seedling orchids of different species with longer watering intervals (2 days, 4 days, and 6 days). The method used was Randomized Block Design (RAK). The results obtained showed that Rhizoctonia mycorrhiza had 2 cell nuclei and had branches with right angles. The application treatment of Rhizoctonia mycorrhiza (M) had a very significant effect on the parameters of plant height growth, the number of leaves, and fresh weight. The treatment of watering time interval (P) had a very significant effect on the parameters of plant height growth, the number of leaves, and plant fresh weight, and affected the number of roots. The combination of Rhizoctonia mycorrhiza application treatment and water application time interval (M x P) showed results that had a very significant effect on the number of leaves parameters and significantly affected plant height. Rhizoctonia mycorrhiza applied to D. stockelbuschii was able to form associations with plant roots by forming a platoon structure.